The name of a queen: William Fleetwood's Itinerarium ad Windsor - Beem, Charles; Moore, Dennis; Fleetwood, William (Queenship and power, 2013)
Introduction : the name of a queene / Dennis Moore -- William Fleetwood's Itinerarium ad Windsor / edited by Dennis Moore -- William Fleetwood and Itinerarium ad Windsor / Charles Beem -- Itinerarium ad Windsor and Robert Dudley, Earl of Leicester / Jacqueline Vanhoutte -- "Marvellously given to be antiquaries" : William Fleetwood's Itinerarium and Thomas Sackville, Lord Buckhurst / Rivkah Zim -- Wading in "the troublesome seas... of antiquityes" : William Fleetwood as antiquary and historian / James D. Alsop -- Itinerarium ad Windsor and English queenship / Carole Levin and Charles Beem -- "Bloody Mary"? : changing perceptions of England's first ruling queen / Sarah Duncan